2015
DOI: 10.1108/ijse-02-2014-0023
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and earning compulsions for the family have pushed children out of schools

Abstract: Purpose – The purpose of this paper is to examine factors that explain dropout of children from primary schools in Lohit district of Arunachal Pradesh, India. Design/methodology/approach – The field survey was carried out in two phases, one, during January to April of 2010 and two, between August and November of 2011. The entire research work is based on stratified random sampling. The population in Lohit district is a set of tribal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Some parents lack awareness of the importance of education, leading them to withdraw children from school (Ud Din et al., ; Cemalcilar & Goksen, ; Banik & Neogi, ) (Pakistan, Turkey, India). The analysis of Banik and Neogi () in India showed that these parents consider education as a waste of money which may make them go hungry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some parents lack awareness of the importance of education, leading them to withdraw children from school (Ud Din et al., ; Cemalcilar & Goksen, ; Banik & Neogi, ) (Pakistan, Turkey, India). The analysis of Banik and Neogi () in India showed that these parents consider education as a waste of money which may make them go hungry.…”
Section: Discussionmentioning
confidence: 99%
“…Some parents lack awareness of the importance of education, leading them to withdraw children from school (Ud Din et al., ; Cemalcilar & Goksen, ; Banik & Neogi, ) (Pakistan, Turkey, India). The analysis of Banik and Neogi () in India showed that these parents consider education as a waste of money which may make them go hungry. Dropout is also prevalent among immigrant households, as observed in Pakistan, Thailand and Turkey (Farid‐ul‐Hasnain & Krantz, ; Korinek & Punpuing, ; Cemalcilar & Goksen, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, a higher proportion of girls among children aged 5-14 was associated with lower probability of a child being involved in child labor as girls were less likely to enter the labor market. Various factors, such as pressures to earn income and engage in household work and other difficulties associated with accessing school, as well as lack of parental awareness about the importance of children's education, are found to explain the dropout of children from school in India (Banki and Neogi 2014). The complex interplay of poverty and demography thus affects the educational experiences of those from poor households.…”
Section: Explaining the Association Between Poverty And Educationmentioning
confidence: 99%
“…The authors of the articles where results pertain to are put in bracket. (Banik & Neogi, 2015;Farid-ul-Hasnain & Krantz, 2010) Males more likely to be pressurised to contribute to family income (Flisher et al, 2010) Under-nutrition, poor health (Siddhu, 2011) Irregular school attendance from being sent home for fees (Zuilkowski et al, 2016) Risk of unwanted pregnancy for girls (Zuilkowski et al, 2016) Limitation of ability to purchase educational materials (Huisman & Smits, 2015;Wudu, 2015;Zhao & Glewwe, 2010)…”
Section: Importance Of the Significant Factors Relating To Early School Leavingmentioning
confidence: 99%